Ultrasonographic and vaginal cytological diagnostics of the Queen - A. P. Pertiwi; L.I.T. A. Tumbelaka; M. F. Ulum (Indonesian Center for Animal Research and Development (ICARD), 2018)
Ultrasonography is a diagnostic method to image the conditions of reproductive organs and it could be supported by vaginal cytology to identify the activities of the ovaries by the types of vaginal exfoliate cells. The aims of this study was to observe reproduction organ through ultrasonography with supportive diagnostic with vaginal cytological assessment. A total of 10 individual queens were used in this study and then grouped into intact group (n=5) and spayed (ovariohysterectomy) group (n=5) based on the anamneses or their medical history. The vagina, cervix, uterus body and horns, and ovaries were imaged and measured by ultrasound. Vagina, uterine body and horn seem as pipe-like structures with hyperechoic outer lines. The lumen in uterine body and horn seem as a hyperechoic structure. The ovaries seem as round- or oval-shaped structures with anechoic follicles. The corpus luteal has thick wall and seen as anechoic in its centre part. The corpus albicans seems as a hyperechoic structure. The vagina of spayed queens seemed more corrugated than those intact queens. The cervix is seen as a hyperechoic structure linking the vagina and uterine body. Exfoliate vaginal epithelial cell types were then also be identified and counted on each queens. The results of vaginal cytology showed that proestrus occured in 3 intact queens, late metestrus in 1 intact and 3 spayed queens, anestrus in 1 spayed queen, and unidentifiable estrus stage in 1 intact and 1 spayed queens. Moreover, the morphology of cervix and uterine was affected by the activity of ovary.